Connective Tissue Growth Factor in Normal and Pathological Processes - S. V. Topolyanskaya (SINAPS LLC, 2020)
Modern concepts about the role of connective tissue growth factor in various physiological and pathological processes are described in the review. Connective tissue growth factor regulates a variety of cellular functions, including proliferation, migration, adhesion, differentiation and synthesis of extracellular matrix proteins in cells of different types. This factor is also involved in more complex biological processes of angiogenesis, chondrogenesis, wound healing, fibrosis and oncogenesis. Increased expression of connective tissue growth factor is observed in different cardiovascular and oncological diseases. Potential role of this growth factor in regulation of cellular senescence and aging processes is also discussed.